Application Of The Use Of Audio Visual Media To Increase Ipa Students In Class Vi Students Of Sdn 014 Rambah Samo For The 2018/2019 Academic Year - Wartini Wartini (Indonesian Journal of Basic Education, 2021)
This study aims to obtain data and information about the application of the use of audio visual media to improve science learning outcomes for class VI SD Negeri 014 Rambah Samo for the 2018/2019 academic year.The type of research used is classroom action research (PTK) which consists of two cycles. This study used audio-visual media consisting of test results and observation sheets used during the research action, then analyzed into planning materials for the next cycle. The data obtained is then processed, in order to draw conclusions. The subjects in this study were students of grade VI SD Negeri 014 Rambah Samo, totaling 29 students, consisting of 20 boys and 9 girls. The results of each cycle carried out in the study showed an increase in student science learning outcomes by applying audio-visual media in class VI SD Negeri 014 Rambah Samo. The mean of students' initial score was 73%, increasing in cycle I to 80% and 86% in cycle II. The expected implication of using audio-visual media can improve learning outcomes and have a positive effect on grade VI SD Negeri 014 Rambah Samo